A Study of the Distinction between Narrative and Textual Time in the Anecdotes of Sa'di’s Golestan - Faezeh Arab Yousefabadi (Matn/Pizhūhī-i Adabī, 2016)
Sa'di's Golestan is a narrative literary work in which the techniques of narrative time have been masterfully employed. This study aims at comparing narrative time and textual time in this literary masterpiece. To do so, based on Gerard Genette’s theory of narratology, the content of Sa'di's Golestan was analyzed for the elements of time. It was found that there were some deviations from the linear course of time in some of Golestan’s narratives. As for the criterion of order, 23 and 2 percent of the whole anecdotes included analepsis and prolepsis respectively. As for duration, 23 percent of the anecdotes contained short and long descriptions. It was also found that there was a synchrony between narrative and textual tine in 16.5 percent of the anecdotes, where the whole story is narrated at a constant speed. It was also found that due to the use of summary technique, 96 percent of the anecdotes are rapidly narrated. This rapid narration was found in 91 percent of the anecdotes that contained ellipsis technique. Finally, as for the criterion of frequency, most of anecdotes had singular frequency, 2% had repetitive frequency and 3% had recounting frequency.